Case report: EBV-positive epithelioid follicular dendritic cell sarcoma with CD30 expression: a highly challenging diagnosis - Chen, Ying; He, Xin; Zhu, Xingyan; Xu, Yujuan; Guo, Deyu (Frontiers in Oncology, 2024)
Introduction: Follicular dendritic cell sarcoma (FDCS) is a rare tumor entity with a wide range of anatomical sites and strong heterogeneity in morphology and immunohistochemistry, making it highly susceptible to misdiagnosis.There are two types of FDCS, conventional FDCS and EBV+ inflammatory FDCS.It is currently believed that the former has nothing to do with EBV infection.Case description: A 69-year-old male patient was admitted to our hospital after 4 months of progressive enlargement of the neck mass. Positron emission tomography/computed tomography (PET/CT) examination showed multiple enlarged lymph nodes in the body. After cervical lymph node excision and biopsy, it was found that the tumor cells were epithelioid and diffusely expressed EBER and CD30. It was initially diagnosed as poorly differentiated cancer and lymphoma. In subsequent differential diagnosis, we found it strongly stained CD21 and CD23 , which was approved the diagnosis of EBV+ FDCS.Conclusions: Epithelioid FDCS is very rare. EBV-positive FDCS with abnormal expression of CD30 has not been reported. Whether EBV also plays an important role in conventional FDCS requires more cases to be verified. Our case provides valuable research clues for further understanding the pathological characteristics of this tumor entity.